Thyroid Heart Disease in Young Male, a Case Report - Sihite, Perdana Liansyah; Hambali, Abdullah; Kamil, Muhammad Firdaus; Muhsin, Muhsin; Gani, Azhari; Diah, Muhammad (CoinReads Media Prima, 2023)
Introduction: The thyroid gland produces thyroid hormones that affect all tissue's metabolic processes, including the heart. Disorders of thyroid hormones, both increasing and decreasing thyroid hormones, can cause similar symptoms to primary heart disease. Thyroid heart disease (THD) is a heart disease that occurs due to increasing (hyperthyroid) or decreasing (hypothyroid) thyroid hormones in the circulation. Hyperthyroidism can cause several types of heart disease, including mitral regurgitation, tricuspid regurgitation, cardiomyopathy, heart failure, mitral valve prolapses, atrial fibrillation or sinus tachycardia. Method: This was a retrospective case report, after analysis of patient clinical data. The patient provided written informed consent to publish their case details and any accompanying images. Results: Almost all cases of THD occur in middle-aged women. Here we presented a 32-year-old male patient diagnosed with THD caused by graves' disease. Patient was admitted to emergency department due to shortness of breath. Medical and non-medical treatments were administered to the patients, and patients experienced improvement after several days of hospitalization. Conclusion: In fact, the progression of hyperthyroidism is characterized by remission and long-term exacerbations. Although some patients can remain euthyroid for a long time after therapy, many eventually get into hypothyroidism. Therefore, lifetime follow-up is an indication for all patients with hyperthyroidism.